[tex]\displaystyle\\
11d)\\
\left(\frac{2}{5}\right)^x: \left(\frac{2}{5}\right)^{-3}=\left(\frac{2}{5}\right)^7\\\\
\left(\frac{2}{5}\right)^{x-(-3)}=\left(\frac{2}{5}\right)^7\\\\
\left(\frac{2}{5}\right)^{x+3}=\left(\frac{2}{5}\right)^7\\\\
x+3 =7\\\\
x = 7-3\\\\
x=\boxed{4}[/tex]
[tex]\displaystyle\\
11e)\\
\left(\frac{8}{27}\right)^x:\left(\frac{2}{3}\right)^4=\left(\frac{2}{3}\right)^8\\\\
\left(\left(\frac{2}{3}\right)^3\right)^x:\left(\frac{2}{3}\right)^4=\left(\frac{2}{3}\right)^8\\\\
\left(\frac{2}{3}\right)^{3x}:\left(\frac{2}{3}\right)^4=\left(\frac{2}{3}\right)^8\\\\
\left(\frac{2}{3}\right)^{3x-4}=\left(\frac{2}{3}\right)^8\\\\
3x-4=8\\\\
3x=8+4\\\\
3x=12\\\\
x=\frac{12}{3}=\boxed{4} [/tex]
[tex]\displaystyle\\
11f)\\
\left(\frac{3}{5}\right)^{15}: \left(\frac{3}{5}\right)^{2x-1}=\left(\frac{3}{5}\right)^6\\\\
\left(\frac{3}{5}\right)^{(15-(2x-1))} =\left(\frac{3}{5}\right)^6\\\\
\left(\frac{3}{5}\right)^{(15-2x+1)} =\left(\frac{3}{5}\right)^6\\\\
\left(\frac{3}{5}\right)^{16-2x} =\left(\frac{3}{5}\right)^6\\\\
16-2x=6\\\\
-2x = 6-16\\\\
-2x = -10~~~\Big| \times (-1) \\\\
2x = 10\\\\
x= \frac{10}{2} = \boxed{5}[/tex]